Current, emerging, and potential therapies for non-alcoholic steatohepatitis - Yang, Zhen; Wang, Lin (Frontiers in Pharmacology, 2023)
Nonalcoholic fatty liver disease (NAFLD) has been confirmed as the most common chronic liver disease worldwide with a growing incidence. NAFLD is considered the hepatic manifestation of metabolic syndrome that arises from multiple factors (e.g., oxidative stress, metabolic disorders, endoplasmic reticulum stress, cell death, as well as inflammation). Nonalcoholic steatohepatitis (NASH), an advanced form of NAFLD, has been reported as a leading cause of cirrhosis and hepatic carcinoma, and it is progressing rapidly. While there is no approved pharmacotherapy for NASH, a considerable number of therapeutic targets have emerged with the deepening of the research on NASH pathogenesis. In this study, the therapeutic potential and properties of regulating metabolism, the gut microbiome, antioxidant, microRNA, inhibiting apoptosis, targeting ferroptosis and stem cell-based therapy in NASH are reviewed and evaluated. Since the single drug treatment of NASH is affected by individual heterogeneous response and side effects, it is imperative to carry out precisely targeted therapy with low toxicity. Lastly, targeted therapeutic agents delivery based on exosomes is proposed in this study, such that drugs with different mechanisms can be incorporated to generate high-efficiency and low-toxicity individualized medicine.